PROTOPLAST FUSION BETWEEN WHITE AND BROWN OYSTER MUSHROOMS - Ira Djajanegara; Agus Masduki (Indonesian Journal of Agricultural Science, 2010)
Genetic crossing of white oyster mushroom (Pleurotus floridae) to introduce longer storage life trait can only be done within individuals in this particular species. However, longer storage life trait is possessed by brown oyster mushroom (Pleurotus cystidiosus). Therefore, a protoplast fusion experiment between white and brown oyster mushrooms was conducted to obtain an oyster mushroom strain showing high productivity and long storage life. The experiment was done at the biology laboratory of the University of Al Azhar Indonesia from May 2008 to August 2009. Protoplast fusion was done by isolating protoplast from 5-day old monokaryotic mycelia grown in potato dextrose broth (PDB). Around 3.15 x 105 protoplasts ml-1 were harvested using mixture of cellulase Onozuka R-10 (1%) and macerozyme R-10 (1%) from brown oyster mushroom with 80.61% viability. Similarly, 3.71 x 105 protoplasts ml-1 were harvested using lysing enzyme (2%) from white oyster mushroom with 83.68% viability. Protoplast fusions were conducted using 40% PEG6000 for 10 minutes. The candidate fusants were then screened using minimum regeneration media (MRM). There were 22 colonies grew on MRM media and four colonies (FS1, FS2, FS3, and FS4) showed clamp connection as well as primordia formation to be chosen as candidate fusants. However, isozyme studies using malate dehydrogenase and acid phosphatase as marker enzymes confirmed that only FS1 and FS2 were the hybridized products. The two colonies showed different mycelia growth patterns and hyphae sizes, fruit body morphology and productivity compared to their parents. These two fusants, however, did not indicate the presence of longer storage life trait as expected despite a higher productivity achieved by FS1. In this study, the protoplast fusion only yielded higher productivity strain of mushroom with different colors without any changes in storage life.